Parental informal occupation does not significantly deter children's school performance: A case study of peri-urban Kathmandu, Nepal - Resham Thapa-Parajuli; Sujan Bhattarai; Bibek Pokharel; Maya Timsina (Economies, 2025)
This paper investigated how parents' informal work relates to their children's academic performance. We interviewed the heads of households with 83 school-aged children in peri-urban Kathmandu to obtain information on parental occupation and child schooling. We also interviewed key informants and conducted focus group discussions to investigate the relationship between working parents' job profiles and their impression of their child's school achievement. Parent characteristics, such as work status (formal or informal), educational attainment, family size, and number of children, were recorded. The primary variable of interest was the children's academic performance, measured as improved or otherwise compared to the previous year. Our analysis confirmed that parents in informal jobs spent more time with their school-going children than their counterparts in formal employment. We found that the parents in informal jobs were relatively more educated in the sample area. The existing literature concurs that parental support significantly influences children's educational outcomes. Parents in informal jobs, while spending more time with their children, expressed pessimism regarding their children's school performance and future opportunities. We also found that household wealth, past performance, school type, and the level of supporter education in the family played significant roles in shaping parental perceptions of the child's school performance. At the same time, we found the nature of the parent's job did not significantly determine the child's school performance, ceteris paribus.
Keywords: 330; informality employment; informal economy; child education